Pros and cons of the multilateral system of international agreements on trade in agricultural products - Spoto, Giuseppe (Przegląd Prawa Rolnego, 2021)
Even though the regulation on the trading in agricultural products has evolved from the objectives of full liberalisation pursued for the trade in industrial products, the GATT rules have been applied to agricultural products from the very outset. The author of this article reconstructs the regulatory framework of international sources, with particular attention to the SPS Agreement (the Sanitary and PhytoSanitary measures), the TBT Agreement (the Technical Barriers to Trade), and the TRIPs Agreement (Trade Related Intellectual Property Rights). The second part of the essay delves into the issue of trade and information to guarantee international humanitarian law, starting from the examination of the Israeli wine case and the reasoning of the Court of Justice of the European Union in its judgment (C-368/18). Since the establishment of the WTO, many changes have taken place, but above all there has been a reversal of direction by the most industrialized countries that have chosen to stimulate bilateral trade treaties over the multilateral system, thus undermining the importance of the WTO rules. The most significant novelty of this evolution is that such bilateral agreements are no longer to be considered as further developments in the construction of the multilateral system, but have often become real obstacles to this reconstruction. For the author, it is precisely those rules of international trade established with the WTO that can offer the best guarantees in the face of trade growth and the ever-increasing conquest of significant shares of the world market by the most aggressive countries. The economic crises of the recent years and, above all, the recent upheaval in international markets following the pandemic have shown the need to renew the global agenda, indissolubly linking the movement of goods (especially agricultural goods) to further objectives that cannot be separated from climate change, the fight against pollution and the solution to environmental problems which have become issues to be considered as pieces of a single large mosaic. These objectives would require a relaunch of multilateralism and confirm the importance of finding a common link within the WTO.